Genome analysis of two novel Pseudomonas strains exhibiting differential hypersensitivity reactions on tobacco seedlings reveals differences in nonflagellar T3SS organization and predicted effector proteins. Issue 2 (21st February 2018) - Tchagang, Caetanie F.; Xu, Renlin; Doumbou, Cyr Lézin; Tambong, James T.
Abstract: Multilocus sequence analysis (MLSA) of two new biological control strains (S1E40 and S3E12) of Pseudomonas was performed to assess their taxonomic position relative to close lineages, and comparative genomics employed to investigate whether these strains differ in key genetic features involved in hypersensitivity responses (HRs). Strain S3E12, at high concentration, incites HRs on tobacco and corn plantlets while S1E40 does not. Phylogenies based on individual genes and 16S rRNA‐ gyr B‐ rpo B‐ rpo D concatenated sequence data show strains S1E40 and S3E12 clustering in distinct groups. Strain S3E12 consistently clustered with Pseudomonas marginalis, a bacterium causing soft rots on plant tissues. MLSA data suggest that strains S1E40 and S3E12 are novel genotypes. This is consistent with the data of genome‐based DNA‐DNA homology values that are below the proposed cutoff species boundary. Comparative genomics analysis of the two strains revealed major differences in the type III secretion systems (T3SS) as well as the predicted T3SS secreted effector proteins (T3Es). One nonflagellar (NF‐T3SS) and two flagellar T3SSs (F‐T3SS) clusters were identified in both strains. While F‐T3SS clusters in both strains were relatively conserved, the NF‐T3SS clusters differed in the number of core components present. The predicted T3Es also differed in the type and number of CDSs with both strains having unique predicted protease‐related effectors. In addition, the T1SS organization of the S3E12 genome has protein‐coding sequences (CDSs) encoding for key factors such as T1SS secreted agglutinin repeats‐toxins (a group of cytolysins and cytotoxins), a membrane fusion protein (LapC), a T1SS ATPase of LssB family (LapB), and T1SS‐associated transglutaminase‐like cysteine proteinase (LapP). In contrast, strain S1E40 has all CDSs for the seven‐gene operon ( pel A‐ pel G) required for Pel biosynthesis but not S3E12, suggesting that biofilm formation in these strains is modulated differently. The data presented here provide an insight of the genome organization of these two phytobacterial strains. Abstract : Multilocus sequence analysis (MLSA) of two new biological control Pseudomonas strains (S1E40 and S3E12) performed to assess the taxonomic positions relative to close lineages showed that these could be novel species. In addition, comparative genomics employed to investigate whether these strains differ in key genetic features. The data presented here provide an insight on the genome organization of these two phytobacterial strains.